Parallel Presentation of Positive and Negative Sides of Igbo Culture in Things Fall Apart (Global Journal of Human-Social Science, 2015)
Chinua Achebe's magnum opus Things Fall Apart reflects authentic presentation of the Igbo society. Various social, political, economic, religious, psychological and personal issues of the Igbo people have been put forward by the author in this ethnographic novel. Achebe has depicted these issues from the perspective of both an observer and a critic. The ethnographic depiction of the Igbo life indicates that Chinua Achebe has tried to maintain his objective stance in the novel. He is not biased at all. It is evident in his contrastive presentation of the culture and beliefs of the Igbo; in one hand, he presents the constructive and rational side of the Igbo, on the other hand, he highlights their follies and irrational beliefs too. Achebe as an original Igbo expectedly presents the riches and potentialities of the Igbo society. But at the same time he is not uncritical of the limitations of his society where he belongs to. The present study has dealt with Achebe's audacious attempt to present the limitations and follies of Igbo life in Things Fall Apart.
Keywords: igbo; objectivity; parallel; duality; multiple voices etc